Analysis Of The Quality Level Of Patients Services In Community Health Center Baktiya Using Fuzzy Servqual Method - Bakhtiar Bakhtiar; Muhammad Zakaria Zakaria; Khairul Anshar Anshar; Fitri Wahyuni Wahyuni (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
Community Health Centers Baktiya is a company engaged in services related to the patient, Thus it is necessary to improve the quality of services provided so that customers feel comfortable and satisfied, and need a method to measure the quality of health services Baktiya. The data collection steps were conducted by observing and distributing questionnaires from several criteria. The criteria are obtained through interviews and literature study. The method used to measure the quality of service using Fuzzy-Servqual. The research instrument used questionnaires with a total sample of 40 respondents, ie outpatients Community Health Centers Baktiya. The results of data processing, obtained that the value of fuzzy-servqual per criteria as a whole has a low value so that Baktiya Health Center needs to make improvements. It also shows that customer expectations are not yet in line with the perceptions of the services they receive. With these results the management of Baktiya Community Health Centers need to immediately improve the quality of service to attract patients. Patient waiting time for service to doctor's office (after registration) and patient waiting time for drug taking (after service in check room).